2020
DOI: 10.20944/preprints202010.0400.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Behavioral Changes During COVID-19 Confinement in France: A Web-Based Study

Abstract: (1) Background: A global pandemic due to COVID-19 emerged in November 2019 and hit France in early March 2020. It not only resulted in a loss of lives but also in very strict confinement measures. The objective of this study was to understand what the determinants of the change in participants’ behavior and mental state were during the confinement. (2) Methods: An online survey was launched on April 23rd, 2020, and closed on May 7th, 2020. The final sample included 1454 participants from 24 to 65 yea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
2
11
0
1
Order By: Relevance
“…Similar assumptions were also made about results from France [ 35 , 36 ] and Australia [ 41 , 43 ], where a tendency towards decrease in alcohol consumption at the end of the lockdown in comparison to the beginning was observed. Results from USA were also differed between the studies [ 17 , 27 , 39 ].…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Similar assumptions were also made about results from France [ 35 , 36 ] and Australia [ 41 , 43 ], where a tendency towards decrease in alcohol consumption at the end of the lockdown in comparison to the beginning was observed. Results from USA were also differed between the studies [ 17 , 27 , 39 ].…”
Section: Discussionsupporting
confidence: 60%
“…A total of 1489 studies were identified through databases and reference searching and after removal of 642 duplicates, 847 studies were screened. Hence, 32 studies [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ] (all cross-sectional) were included in this systematic review. Characteristics of the 32 cross-sectional included studies can be found in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mixed results within a study were also available from Italy where one study reported both perceived improvements (34%) and declines (19%) [9]. Improvements in overall dietary quality were available from Saudi Arabia [40], Brazil [41], Canada [42], and Spain (via a closer adherence to a Mediterranean-style diet [43,44]).…”
Section: Dietary Patternsmentioning
confidence: 99%